An ion migration induced self-powered photoelectrical detector based on FAPbBr3 single crystals. Issue 11 (24th February 2022) - Dong, Song-Tao; Fu, Zhuang; Yu, Miaocheng; Jiang, Jia-Ling; Jin, Xiaoyun; Guo, Yu-Hang; Wang, Lei; Zhang, Ya-Mei
Abstract : Irreversible ion migration was utilized to design a built-in electric field and energy band bending in a symmetrically structured Au/FAPbBr3 /Au device, which successfully leads to a self-powered photoelectric device based on FAPbBr3 crystals. Abstract : Self-powered photoelectric devices as a new type of sensor without an external power source have a great potential advantage in the next generation of portable and wearable personal devices. The design of those devices is normally based on three kinds of strategies: a p–n junction, the Schottky junction and ferroelectric polarization. Here, a novel solution based on ion migration induced self-powered photodetectors was explored. In this work, high quality halide perovskite FAPbBr3 crystals were grown by an inverse temperature crystallization (ITC) method. An irreversible ion migration was intentionally created using a symmetrically structured Au/FAPbBr3 /Au device. The resulting built-in electric field and energy band bending were proved using electrical measurements in the dark and under light. Finally, the response of the ion migration induced self-powered FAPbBr3 detector was investigated with the values of R (∼0.18 mA W −1 ) and EQE (∼0.055%) under light with a power density of 1 mW cm −2 and a wavelength of 397 nm. Our investigation demonstrates that ion migration, which is normally deemed a detrimental factor for device stability, can be intentionally used for self-powered photoelectric devices.